Controversies about botulinum toxin type A duration effect - Alcolea, Justo; García Monforte , Fernando (Aesthetic Medicine, 2025)
Botulinum toxin is a commonly used treatment in aesthetic medicine. However, physicians have expressed concerns about the brief duration of the toxin’s effect on patients. Nonetheless, the manufacturers and distributors of the toxin deny any manufacturer-dependent cause for the shortened efficacy of the toxin. The aim of this paper is to analyse the possible causes that may influence the duration of action of botulinum toxin through an extensive review of published articles on the subject. The causes of the condition may be linked to the patients’ immune response or non-immune factors. These factors include the association of toxins with accompanying proteins, which can affect the neuromuscular receptors, as well as the patient’s emotional expression through gesticulation, toxin reconstitution, or the injection technique performed. In conclusion, to achieve positive outcomes, it is essential to consider potential factors that may adversely affect the duration of the effect, conduct a thorough patient assessment, administer treatments at safe intervals, and avoid using questionable toxins.